Detection of antibodies against canine distemper virus in jaguars (Panthera onca) and pumas (Puma concolor) in Madre de Dios, Peru - Atauje S., José (2019)
The objective of the study was to determine the presence of antibodies against canine distemper virus (CDv) in jaguars (Panthera onca) and pumas (Puma concolor) of free life in Madre de Dios. The 19 samples (jaguars = 13, pumas = 6) were collected at the Río Los Amigos Conservation Concession (n=2) and the Tambopata National Reserve / Bahuaja Sonene National Park (n=17) during the routine activities of the World Wildlife Fund (WWF) in 2006-2008. The detection of antibodies against the CDv was carried out by the indirect immunofluorescence test (IFAT) in a dilution of 1:50. All free-living wild cats were negative for antibodies to CDv. The results indicate that these cats were not exposed to CDv.